Revision of Plumarius Philippi 1873 (Hymenoptera: Chrysidoidea, Plumariidae) from Argentina north of Patagonia, with description of eighteen new species - Diez, Patricia Alejandra (2016)
Twenty six species of Plumarius from Argentina north of Patagonia are revised. Eighteen new species: Plumarius politus sp. nov., P. sarophorus sp. nov., P. globulosus sp. nov., P. angulatus sp. nov., P. noa sp. nov., P. divergens sp. nov., P. malaris sp. nov., P. gracilior sp. nov., P. riojanus sp. nov., P. exophthalmus sp. nov., P. planatus sp. nov., P. albinervis sp. nov., P. truncatus sp. nov., P. mikrommatus sp. nov., P. obscurus sp. nov., P. gracilis sp. nov., P. fidalgoi sp. nov., and P. ocellulatus sp. nov. are described and illustrated. A new record for known species as well as a key to 26 known species in the region is given. A redescription of P. tumidulus Papp, 2000, which is the first record of the family Plumariidae from Uruguay, is done.